Faroese sheep expand overall global ovine genetic diversity - Eva Kjæld Hansen; Jens Ivan í Gerðinum; Dag Inge Våge; Svein-Ole Mikalsen (BMC Genomic Data)
Abstract Background Faroese sheep have an unclear history. While it is assumed that the Vikings brought sheep to the Faroes, traces of pre-Viking age sheep are also found. Historical sources cite disasters in a period around year 1600 that essentially eradicated the sheep population, and subsequent imports from Iceland to the northern part of Faroes, and from Shetland and Orkneys to the southern part of Faroes. We have here investigated the genetic relationship of northern Faroe sheep with other breeds. Results A total of 359 sheep from four flocks from three Faroese islands (Streymoy, Eysturoy, Kalsoy) were genotyped using the GeneSeek Genomic Profiler Ovine 50K chip. The samples were clearly stratified into three groups corresponding to island of origin. This is likely due to the minimal transport of animals between the islands during extended periods of time. The Faroese samples were compared with the data from the Sheep HapMap database, representing breeds from different parts of the world, and, additionally, Norwegian White Sheep. The Northern European short-tailed breeds clearly stood out from the remaining global breeds, and Faroese sheep gained a peripheral position among the other North Atlantic short-tail breeds, with Icelandic sheep and Norwegian spael as their closest neighbors. The peripheral position suggests that the link to the surrounding breeds might be more distant than expected. Conclusions Despite known imports of sheep from neighboring countries after the year 1600, this is poorly reflected in the genotyping data. One possible explanation could be that the present-day Faroese sheep have an unbroken genetic link to the pre-year 1300 Faroese sheep (which possibly were a mix of old-Norse and old-British/Irish animals), regardless of the presumed post-year 1600 influence from other breeds in the North Atlantic region.